行星齿轮机构的虚拟装配方法研究 - 田雨; 何卫东; 张迎辉; 吴鑫辉 (Jixie chuandong)
For solving the problem of correct position in planetary gear mechanism,aiming at the interference problem of planetary mechanism for single planetary gear,the basic method of aligning the planes and confirming the assembly relationship is proposed.Aiming at the assembly problem of many planetary gears,the formula of planetary gear relative angles in installation stage is deduced,and a method of virtual assembly of planetary mechanism with many planetary gears is proposed.Finally,taking the RV250reducer as example,no inference assembly is accomplished,which is the foundation of mechanism motion and dynamics analysis.